HALANGAN-HALANGAN PELAKSANAAN UNDANG-UNDANG JENAYAH ISLAM DI DALAM PERLEMBAGAAN MALAYSIA - Bari, Abdul Aziz (Jurnal Syariah, 2019)
This essays attempts to highlight some of what is seen as obstacles presented by the constitutional framework in Malaysia that makes the implementation of full-fledged Islamic laws in the country either difficult or impossible. The article argues that it is not something that is inherent in the framework and that it is not insurmountable. The article also argues that part of the so-called obstacles are actually political and thus requires political will to solve. Thus far there have been many instances whereby the constitution has been set aside or amended to make what is desired by the powers that be work; and this strengthens the thesis argued by the author.